Investigation of Toxoplasma infection in zoo animals using multispecies ELISA and GRA7 nested PCR - Ru-Min Liu; Wei-Hsiang Huang; Shang-Lin Wang; Sin-Ling Wang; Pei-Yun Huang; Chen-Yeh Lien; Yen-Hsueh Lai; Pao-Jung Wang; Li-Hsin Wu; Albert Taiching Liao (BMC Veterinary Research, 2022)
Abstract Background Toxoplasma is an obligate intracellular protozoan that causes an important zoonotic disease with a worldwide distribution. Felids are the definitive hosts of this parasite, while virtually all warm-blooded animals, including birds, serve as intermediate hosts. Four ring-tailed lemurs (Lemur catta) in the Taipei Zoo died of acute Toxoplasma infection in June 2019. Since then, Toxoplasma has occasionally been identified in this Zoo during necropsy of dead animals and PCR of animal blood samples. Therefore, a general survey of Toxoplasma infection in animals in the Zoo seems to be needed. Methods and results An indirect multispecies ELISA was used for the first time to screen for Toxoplasma infection in 326 serum samples collected from 75 species of animals. The infection rate of Toxoplasma was 27% (88/326). A commercial latex agglutination (LAT) assay was used to re-examine the samples with doubtful and uncertain ELISA results (151 samples from 42 species). The infection rate increased to 36.2% (118/326), and the indirect multispecies ELISA appeared to be applicable to 31 of 75 species animals included in this study. Nested PCR assays targeting the dense granule protein 7 (GRA7) gene and B1 gene were also used to detect Toxoplasma in DNA samples extracted from 10 liver or blood specimens from 8 animals. GRA7 gene fragments were amplified from 8 samples from 7 animals, while B1 gene fragments were amplified from only 4 samples from 4 animals. From the B1 nested PCR and the sequence data of GRA7 fragments amplified from infectious specimens, the animals in the Zoo were speculated to have been infected by at least three different Toxoplasma variants. Conclusions According to the serological investigation, we speculated that over one-third (36.2%) of animals in Taipei Zoo presented the infection of Toxoplasma, and the indirect multispecies ELISA we used can be applied to detect Toxoplasma infection in 31 animal species included in this study. Sequence analysis revealed that at least three Toxoplasma variants were infecting the animals of Taipei Zoo.